Pelaksanaan Pembelajaran Dengan Pendekatan Aktif Learning Dalam Pelajaran Ekonomi Pada SMU Negeri Di Yogyakarta - Tejo Nurseto (Jurnal Ekonomi dan Pendidikan, 2009)
This research was aimed to describe (1) the implementation of Active Learning at State Senior High Schools in Yogyakarta, (2) the treasury in the implementation of the curriculum and, (3) the dominant factors in its accomplishment.The approach employed in this study was qualitative with the ethnographic method and the research setting was SMAN 3 Yogyakarta, SMAN 9 Yogyakarta and SMAN 11 Yogyakarta. The data were collected through observation, interviews, and documentation. The analysis techniques included the analyses of domain, taxonomy, components, and themes. The validity of the data was tested by lengthening the study and by triangulation.This research findings show the following results:1) in implementation of the Active Learning: a) most of teacher and student who agreed with it, b) there was a few student did not agree with it, 2)The treasuries of the implementation of the Active Learning at SMAN 11 were a) the quality of human resources: teachers, administrative staff and students, b) the National Examination to hamper the implementation of Active Learning in class XII c) the availability of OHP in every class, d) too many learning groups, and e) minimum teachers welfare. The treasury of the implementation of the Active Learning at SMAN 9 were that: a) the school area was narrow and dried so it was not possible to perform theout-door learning activities, b) the students were less active and motivated for learning especially social science majors, c) there was a handicap in financial matters, d) there was less variety in using learning media, and e) most of the equipment in the laboratory was broken and could not be used. The treasuries in the implementation of the Active Learning at SMAN 3 were that: a) the Active Learning is not yet officially ratified, b) the understanding of teachers about the Active Learning was rather low, and c) it was difficult to change the habit of teachers in teaching from teacher-centered to student-centered approach. The most dominant factors in the implementation of the Active Learning at SMAN 11 were a) the leadership of the school principal, b) good team work, and c) teachers and students creativity. The most dominant factors in the implementation of the Active Learning at SMAN 9 were a) the commitment and spirit of the school society to implement Active Learning, b) teacher and student factors, and c) facilities of the school. The most dominant factors in the implementation of the Active Learning at SMAN 3 were a) student factors, b) teacher factors, c) school management and d) the facilities of the school.